Os meios alternativos de solução de conflitos: uma análise da mediação da COECV nos conflitos por terra na Maranhão. - Mendes, Dyhelle Christina Campos (2022)
Before the search for social pacification, mediation has become a tool in different fields, in order to prioritize by consensus as an alternative means of conflict resolution. In this mainstay, the State Commission on Violence in the Countryside and in the City (COECV: abbreviation in Portuguese language), established by Ordinary Law n. 10.246/2015, presents itself as a permanent public policy in Maranhão state context, based on mediation and traversing the multiport justice system. However, before the commission using the delegated scope of the state in order to solve the land collective disagreements, the following question arises: on the basis of the COECV, are the alternative means of conflict resolution appropriate ways to resolve land collective disagreements? For this, the bibliographical research and the ethnography of documents were listed as methodology, based on the reports developed by the committee between 2016, 2017, 2018, 2019, 2021s years, in addition to 2016 and 2020 Internal Regulations and the created law. In relation to specific objectives of the academic production, they are important to examine the use of mediation as a way of resolving collective land disputes with the support of COECV; check the ADRs use in land collective conflicts; and analyze ADRs like a way to resolve conflicts to keep the social pacification. For this, Nader (1994) formulations were used, in relation to her criticisms of the ideology of harmony. In what concerns the justification, it is necessary to check a commission in addition to dealing with sensitive rights, such as dwelling and human rights, it creates the mediation as a suitable to solve this land conflicts, it is necessary to ask, because the research considers the public politics created in Maranhão state scenery. Analyze its workability, therefore, it is contributed with the own company. The answer to the question asked in the beginning is that it is impossible to reach taxing responses, although the commission presents benefits, but it cannot be said the consensus is the most appropriate way in all these situations. What can be said, social pacification as a solution alternative means cannot be used like a criterion silencer of these collectivities, faced with the socioeconomic vulnerabilities found. The mediation cannot be examined without the due guarantees of respect and isonomy of involved parties. Therefore, ADRs cannot be seen canonized as the single way to land conflict solutions, just the Judiciary is not, in this way, we can have a multiport justice system.